The effect of different sizes of shredded newspaper on Compressive strength of mortar - Muhammad Hanif, Mohamad Sharif (2016)
Usage of natural sand as fine aggregate in the concrete mixture industry has become too dependent of this natural resource which took time to be produced. At the same time, production of paper has led to cause the dumping of rubbish in the world is increasing day by day. The objectives of this research are to investigate the properties of mortar using waste newspaper to substitute a portion of fine aggregate. This is one of the approaches to reduce the usage of natural resource and amount of waste paper dump at the landfill. This research used to investigate the effect of different sizes of shredded newspaper on mortar when the specimens were subjected to compression strength test and water absorption test. The mix design used is normal mortar mix which 1:2 ratio of cement and water respectively in addition of wet shredded newspaper with comes with two sizes collected from two offices in Universiti Malaysia Pahang. The size of the cube is 100x100 mm were cured with two types of method that are inside and outside room temperature before undergoing tests. The finding shows that specimens containing bigger size of shredded newspaper have higher compressive strength than smaller size. It is also observed that specimens with smaller size of shredded newspaper has lower rate of water absorption compared to specimens containing bigger size of shredded newspaper.